Optoelectronic investigation of monolayer MoS2/WSe2 vertical heterojunction photoconversion devices. (December 2016) - Cao, Guoyang; Shang, Aixue; Zhang, Cheng; Gong, Youpin; Li, Shaojuan; Bao, Qiaoliang; Li, Xiaofeng
Abstract: Atomically thin transition metal dichalcogenides (TMDs) have gained much attention due to their unique optoelectronic properties. However, besides the plenty of experimental attempts, the optoelectronic simulation, which is useful for uncovering the underlying optical, physical and material mechanisms and promoting the high-performance device designs, has seldom been reported. In this study, addressing the unique device and optoelectronic response of the atomically thin TMD devices and taking the atomically thin MoS2 /WSe2 vertical heterojunction as an example, we present a comprehensive optoelectronic simulation which considers the light-trapping as well as the internal carrier generation/transport/collection processes. The optoelectronic simulation provides a convenient way to study the multi-domain responses of the extremely thin optoelectronic devices. Based on the simulation technique, the energy diagrams, the depletion region, the internal electric field distribution, carrier distribution, etc., have been investigated; moreover, we proposed a metallic-cavity-coupled design for the atomically thin MoS2 /WSe2 devices which exhibits significantly improved optical absorption, higher photocurrent and increased photoconversion efficiency. Graphical abstract: Current-voltage response of the atomically thin N-MoS2 /P-WSe2 photoconversion devices. Highlights: Optoelectronic modeling is presented for atomically-thin PN devices. Intrinsic optoelectronic responses of PN MoS2 /WSe2 devices are examined carefully. Metallic microcavity design improves the optoelectronic performance substantially.